Designing Smart-Contract-Enabled Liquidity Management for Wholesale Rupiah Digital: A Design Science Research Approach - Satria Rana Dityantomo; Made Harta Dwijaksara (Journal of Information System and Informatics, 2026)
This study proposes a smart-contract-enabled liquidity management reference architecture for Bank Indonesia's Wholesale Rupiah Digital (wRD), addressing a gap in Project Garuda where the Proof-of-Concept adopts a gross settlement model supplemented by decentralized queueing but lacks a liquidity-saving mechanism. Using Design Science Research (DSR), a Multivocal Literature Review (MLR) was conducted to synthesize eight academic and grey literature sources that include central bank reports, BIS publications, and industry white papers. Five key takeaways were extracted and mapped to architectural modules. The resulting architecture operates on a unified ledger and comprises five modules: a Policy & Criteria smart contract for participant eligibility and compliance, a centralized Queue smart contract with configurable release rules, a Liquidity-Saving Mechanism (LSM) for periodic multilateral netting, an Automated Liquidity Provisioning (ALP) module for just-in-time intraday repo against tokenized bonds when netting is insufficient, and a guarded Automated Market Maker (AMM) for cross-currency settlement. The architecture is illustrated through a payment state lifecycle with two scenario transaction walkthroughs and assessed through a criteria-based analytical evaluation that verifies design completeness against requirements. Empirical validation through prototyping, simulation, or expert review is left for future work. The main contribution is a literature-derived reference architecture that integrates global CBDC mechanisms adapted to Indonesia's context.